Socio-demographic factors related to parent engagement in the NICU and the impact of the SENSE program. (December 2021) - Whitehill, Laura; Smith, Joan; Colditz, Graham; Le, Tiffany; Kellner, Polly; Pineda, Roberta
Abstract: Background: Early parent engagement in the neonatal intensive care unit (NICU) is important for both parent and infant mental health and for improving developmental outcomes. It remains unclear how different programs, such as the Supporting and Enhancing NICU Sensory Experiences (SENSE) program, may empower parents from various socio-demographic groups to engage in the NICU. An improved understanding could aid in individualizing interventions for those at the highest risk for health disparities. Aims: This exploratory study, which was part of a larger study, sought to explore 1) socio-demographic factors related to parent presence and engagement in the NICU and 2) if the SENSE program related to increased parent presence and engagement among different socio-demographic groups. Methods: Seventy parent-infant dyads (born ≤ 32 weeks gestation) were randomized to SENSE programming (parent education and age-appropriate, positive sensory interventions for parents to conduct with their infants every day of hospitalization) or standard care after admission to the NICU. The amount of parent presence and participation in sensory activities was tracked using bedside logs, nursing records, and research team documentation. Results: Being married ( p  = 0.048; p  = 0.01), having private insurance ( p  < 0.001; p = 0.01), and having fewer children ( p  = 0.004; p  = 0.03) related to more parent presence and engagement respectively. Parents who were Black had less presence and engagement in the NICU ( p  = 0.04; p  = 0.02). Participation in the SENSE program was related to more parent presence and engagement among younger mothers ( p  = 0.002; p  ≤0.001) and among parents living farther distances from the hospital ( p  < 0.001; p  = 0.004). Conclusion: Programming, such as the SENSE program, can improve parent engagement in the NICU among high-risk groups. Highlights: There was more presence and engagement There was more presence and engagement among married, privately insured parents who had fewer children and were not Black. SENSE programming increased presence and engagement in younger mothers and those living farther distances from the hospital. SENSE shows promise for improving parent engagement and outcomes for those who traditionally experience health disparities.